Control of the dental plate in patients with orthodontics. A review of literature - Sánchez Vásquez, Nelly Liliana (2019)
As the orthodontic treatments have been increasing, the pathologies resulting from poor plaque control have also increased while the laps of the treatment ; There is a considerable increase in the appearance of caries or white spots after orthodontic treatments as well as periodontal disease. The control of plaque is extremely important since when presenting orthodontic attachments we diminish the capacity self-cleaning as well as we increase the retentive zones and prone to the formation of the biofilm. To prevent patients from presenting this problem, it is decided to make a bibliographic review and thus propose an alternative for the clinician.